2015
DOI: 10.1074/jbc.m115.651489
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Galectin-3, a β-Galactoside-binding Lectin, to MUC1 Protein Enhances Phosphorylation of Extracellular Signal-regulated Kinase 1/2 (ERK1/2) and Akt, Promoting Tumor Cell Malignancy

Abstract: Background: Both MUC1 and galectin-3 are overexpressed in various malignant tumors. Results: Binding of galectin-3 to MUC1 enhances the phosphorylation of ERK1/2 and Akt, promoting tumor cell malignancy. Conclusion: MUC1-mediated signal transduction occurs through direct binding of galectin-3 to MUC1. Significance: Our findings will provide a new insight into the promotion of MUC1-mediated tumor cell malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 57 publications
1
47
1
Order By: Relevance
“…Revealing the function of galectins and glycoconjugates during blastocyst implantation and the pathogenesis of ectopic pregnancy requires identfication of the glycoconjugates, especially those carrying α2,6‐sialyltion. Mucin 1 (MUC1) is recognized by galectins (Jeschke et al, ; Mori et al, ), making it a candidate glycoprotein that may associate with galectins in the Fallopian tube and uterus. MUC1 is a highly glycosylated protein whose decreased surface expression allows blastocysts to implant at the endometrium in normal pregnancy as well as on the Fallopian tube epithelium in tubal ectopic pregnancy (Aplin et al, ; Savaris et al, ; Al‐Azemi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Revealing the function of galectins and glycoconjugates during blastocyst implantation and the pathogenesis of ectopic pregnancy requires identfication of the glycoconjugates, especially those carrying α2,6‐sialyltion. Mucin 1 (MUC1) is recognized by galectins (Jeschke et al, ; Mori et al, ), making it a candidate glycoprotein that may associate with galectins in the Fallopian tube and uterus. MUC1 is a highly glycosylated protein whose decreased surface expression allows blastocysts to implant at the endometrium in normal pregnancy as well as on the Fallopian tube epithelium in tubal ectopic pregnancy (Aplin et al, ; Savaris et al, ; Al‐Azemi et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, MUC1-C has the capacity to promote loss of polarity with induction of the epithelial-mesenchymal transition (EMT) [3, 4] and thereby interact with other cell surface molecules, including receptor tyrosine kinases (RTKs) [512]. The available evidence has further supported the premise that (i) MUC1-C functions in activating multiple pathways linked to EMT, self-renewal and survival, and (ii) the overexpression of MUC1-C, as found in diverse human carcinomas, represents a subversion and appropriation of these functions by cancer cells to promote their own growth and immortality [1, 13].…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in metastatic processes and in cancer drug resistance . Indeed, it has been shown that Gal‐3 is overexpressed with its ligand MUC1 in malignant tumor cells and induces MUC1 clustering on the tumor cell surface by binding to the TF tumor‐associated antigen . Taking advantage of the Gal‐3 CRD–MUC1 interaction, tumor cells, like intravascular malignant cells, invade vessels and survive in the circulation avoiding anoikis .…”
Section: Introductionmentioning
confidence: 99%